Understanding and responding to HIV/AIDS-related stigma and stigma and discrimination in the health sector - Foreman, Martin [et al.] (PAHO WashingtonUS, 2003)
Analyzes the components of HIV/AIDS-related stigma and discrimination in the health sector. Looks at how they relate and where gaps in knowledge exist. Compares studies of stigma and discrimination, and projects designed to reduce their incidence and impact. Outlines strategies for a comprehensive response. Makes extensive references to Latin America and the Caribbean.